Development of a dehydrated protein food product for military personnel - Masliichuk, Olia; Kushniruk, Halyna (Technology audit and production reserves, 2025)
The object of research is the process of developing a dehydrated protein food product enriched with lupine flour, intended for nutrition of military personnel in extreme conditions. The use of lupine flour is promising in technologies to produce dehydrated products for military personnel. It contains more protein than other legumes and has a less pronounced effect on the organoleptic quality of finished products. It was determined and experimentally proved that white food lupine is a protein enricher in the diet of military personnel, which allows authors to obtain a combined meat and vegetable product balanced in chemical composition. The average protein content in lupine flour is 36–40 % by dry matter, which is 3 times higher than that of first-grade wheat flour and 2.2 % higher than that of soybean flour. A recipe for experimental meat and vegetable protein minced meat with 10 % beef meat substitution was developed. It was found that with an increase in the content of lupine flour in the minced meat, the protein content increases to 10.3 %. It was found that the meat and vegetable protein minced meat of the experimental sample corresponds to the control in taste, smell, color, consistency, but is better in juiciness and has a high rating. The microstructure of the developed meat and vegetable protein minced meat was determined. A technological scheme of production was drawn up and a volunteer test of the production of a dehydrated food product in the diet of military personnel based on meat and vegetable protein minced meat was conducted. The hygienic control of the production of health food products for military personnel was carried out. The express method of hygienic quality control showed that the luminometer readings were within the range of 1.356–1.793 RLU, which is clean, confirming compliance with the hygienic standards of the technological process. The technology of a health product for nutrition of the military personnel of the Armed Forces of Ukraine in extreme conditions was developed. The influence of lupine flour on the protein content in the technology of meat and vegetable protein health-improving minced meat was scientifically substantiated. The possibility of introducing the technology into the diet for dry rations, according to Norm No. 10 for military personnel, was confirmed.